MASLAHAH BASED MEASUREMENT ON INDONESIA ISLAMIC BANKS - Aam Slamet Rusydiana; Hendri Tanjung; Lina Marlina (IJIBE (International Journal of Islamic Business Ethics), 2018)
Every single effort or process taken by Islamic bank to maximize output should also uphold Islamic values, so that maqashid sharia (maslahah-sharia objectives) would be authomatically achieved. There were some research conducted to measure Islamic bank performance using maqashid sharia framework. However, these studies were not explicitly addressing the issue of cost-saving strategies within the framework of efficiency measurement. It is therefore this paper aims to  have  efficiency  and  maslahah  measurement  in  one assessment framework  that  is  maslahah-eficiency  quadrant  (MEQ). There are three aspects measurement of maslahah, namely education, justice, and welfare as maqashid sharia index (MSI). Hence, in order to measure efficiency level of Islamic Banking Industry especially Sharia Business Unit, this study use Data Envelopment Analysis (DEA) method and employ Banxia Frontier Analyst 3.1 for data analysis. Within the MEQ framework, the study revealed that Permata, CIMB, BTN, DKI, Jambi, and Kalbar are excellent since both are within the first quadrant.Whereas Maybank, NISP, Sinarmas, Sumbar, and Sulselbar are considered good at the second quadrant; Danamon, Jatim, Sumut, Riau&Kepri, Kalsel, and Kaltim are fair at the third; and DIY, Jateng, and NTB are poor at the fourth sequentially. It is urge for Islamic bank that are in low level of MSI to have a critical policy to keep in line with the five factor of maqashid sharia apart of having efficiency in order to reach maslahah. keywords: Maslahah-Efficiency Quadrant (MEQ), Maqashid Sharia index (MSI), DEA, Islamic Bank